Pengaruh Komitmen Organisasi dan Kepuasan Kerja Terhadap Organizational Citizenship Behavior (OCB) pada Pegawai Puskesmas Pasimarannu Kabupaten Kepulauan Selayar : The Effect of Organizational Commitment and Job Satisfaction on Organizational Citizenship Behavior (OCB) in Pasimarannu Health Center Employees, Selayar Islands Regency - Salam, Dewi Syafia; Haeruddin, Haeruddin; Hamzah, Wardiah (Journal of Aafiyah Health Research (JAHR), 2025)
Abstrak Latar Belakang: Kekurangan tenaga kerja karena kurangnya komitmen organisasi dan ketidakpuasan tenaga kerja menyebabkan tenaga kesehatan tidak hanya melakukan tuntutan tugas yang terkandung dalam tugas pokoknya atau biasa disebut in-role, namun pegawai disarankan memiliki inisiatif untuk melakukan pekerjaan tambahan diluar tuntutan tugasnya atau biasa disebut extra role. Perilaku extra role dalam organisasi tersebut biasa dikenal dengan istilah Organizational Citizenship Behavior (OCB). Tujuan: Mengetahui Pengaruh Komitmen organisasi dan kepuasan kerja terhadap Organizational Citizenship Behavior (OCB) pada Pegawai Puskesmas Pasimarannu Kabupaten Kepulauan Selayar. Metode: Penelitian kuantitatif dengan pendekatan cross sectional study. Jumlah sampel sebanyak 128. Metode pengumpulan data dengan menggunakan kuesioner.  Analisis data menggunakan analisis univariat dan bivariat. Hasil: sebagian besar  responden berusia  antara 21 hingga 30 tahun (54.69%), berjenis kelamin perempuan (85.16%), masa kerja > 5 tahun (50.78%), tingkat pendidikan D3 (69.53%), status pegawai kontrak (62.5%), bekerja di unit kerja tenaga paramedis (82.03%). Hasil analisis bivariat menunjukkan terdapat pengaruh antara komitmen organisasi dan Organizational Citizenship Behavior (OCB) (p= 0.024), terdapat pengaruh antara kepuasan kerjadan Organizational Citizenship Behavior (OCB) (p=0.010), serta terdapat pengaruh   komitmen organisasi dan kepuasan kerja terhadap Organizational Citizenship Behavior (OCB) (p=0.002).     Kesimpulan: Terdapat pengaruh komitmen organisasi dan kepuasan kerja terdahap  Organizational Citizenship Behavior pada pegawai puskesmas pasimarannu.    Abstract Background: The lack of manpower due to lack of organizational commitment and worker dissatisfaction causes health workers to not only carry out the demands of the tasks contained in their main duties or commonly called in-role, but employees are advised to have the initiative to do additional work outside the requirements called or commonly called extra role. Extra role behavior in the organization is commonly known as Organizational Citizenship Behavior (OCB). This study aims to determine the influence of organizational commitment and job satisfaction on Organizational Citizenship Behavior (OCB) of Pasimarannu Health Center employees, Selayar Islands Regency. Objective: Knowing the Influence of Organizational Commitment and Job Satisfaction on Organizational Citizenship Behavior (OCB) on Employees of Pasimarannu Health Center, Selayar Islands Regency. Method: This type of research is quantitative with a cross-sectional study approach. The number of samples is 128. Data collection using a questionnaire. Data analysis using univariate and bivariate analysis. Results: that most respondents were aged between 21 and 30 years (54.69%), female (85.16%), work period > 5 years (50.78%), D3 education level (69.53%), contract employee status (62.5%), working in a paramedic work unit (82.03%). The results of the bivariate analysis showed that there was an influence between organizational commitment and Organizational Citizenship Behavior (OCB) (p = 0.024), there was an influence between job satisfaction and Organizational Citizenship Behavior (OCB) (p = 0.010), and there was an influence of organizational commitment and job satisfaction on Organizational Citizenship Behavior (OCB) (p = 0.002). Conclusion: There is an influence of organizational commitment and job satisfaction on Organizational Citizenship Behavior on employees of the Pasimarannu Health Center.